Can The “New Normal” Cause Sleep Bruxism in Children-A Review - GURUNATHAN, DEEPA; MS, NIVEDHITHA; MOSES, JOYSON; MATHEW, MEBIN GEORGE; RAMAKRISHNAN, MAHESH (The journal of contemporary issues in business and government, 2020)
COVID-19 has resulted in national lockdown in various countries which has resulted in most citizens of those countries to remain at home. With the lack of social interaction and increase of boredom, children are extremely prone to be irritated and agitated. This can result in bruxism which is clinically manifested by clenching of teeth. Though not life threatening, bruxism can result in various deleterious effects which can affect the quality of life of individuals. Many children who have bruxism have been known to continue the habit as they become adults, resulting in unwanted visits to the hospital. This can be possible only if doctors, parents and children have knowledge about bruxism. With stress and strain increasing during the spread of COVID-19, there is a high chance that most practioners and parents have missed out in identifying bruxism in children. Parents themselves have been found to be anxious and occupied with “work at home” which can result in them being occupied and paying less attention to their children as the workspace and home space have been merged into one area which was not so common before the emergence of COVID-19. Hence this review was undertaken to illustrate how various factors which have become the ‘new normal’ due to COVID-19 can result in sleep bruxism in children